Photometric study and search for variable stars in the intermediate-age open cluster NGC 2126. Issue 2 (19th July 2018) - Chehlaeh, N; Mkrtichian, D; Lampens, P; Komonjinda, S; Kim, S-L; Van Cauteren, P; Kusakin, A V; Glazunova, L
ABSTRACT: We present the results of an analysis of photometric time-series observations for NGC 2126 acquired during the years 2004, 2013, and 2015. NGC 2126 is an intermediate-age open cluster which has a population of stars inside the δ Scuti instability strip. The main purpose is to search for new variable stars, to study their light curves and pulsation spectra. Eleven variables are reported, two of which are new discoveries, eight are pulsating and three eclipsing binary stars, one of which has a pulsating component (V551 Aur). Our 10 times of light minimum along with others compiled from the literature were used to revise the orbital period of V551 Aur: P orb = 1.1731752(8) d. The Wilson–Devinney technique was used to analyse its light curves and to determine a new set of the system's parameters. We found a single pulsation period P pul = 0.12964977(3) d in the residuals which lies near the 9th harmonic of the orbital period. We determined the accurate value of high proper motion star LHS 1809 as μα cos δ = 115.7± 0.1 mas yr −1 and μδ = −823.7 ± 0.1 mas yr −1 . From the construction of the colour–magnitude diagram, we estimated the physical parameters of the cluster. We found that the shape of the colour–magnitude diagram at the turn-off point is well reproduced with an isochrone with log( t ) of 9.1 ± 0.1 yr, metallicity of 0.019, E ( B − V ) = 0.27± 0.01 mag, and ( m − M )0 = 10.80 ± 0.05 mag.